2019
DOI: 10.1177/1350650119896170
|View full text |Cite
|
Sign up to set email alerts
|

Wear analysis of waste marble dust-filled polymer composites with an integrated approach based on design of experiments and neural computation

Abstract: Waste marble dust is a solid waste generated during the cutting and polishing of marble pieces in construction sites and also in marble processing industries. This paper reports on the utilization of this waste as a filler material in particulate-filled polymer composite. Polyester-based composites are prepared with different weight proportions of waste marble dust and the dry sliding wear behavior of these composites is studied. Wear trials are conducted using a pin-on-disc test apparatus based on the Taguchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Analysis of these results leads to the conclusion that combination of factors A4 (20 wt% MD), B1 (400 m sliding distance), C1 (1 m/s sliding velocity) and D1 (10 N normal load) gives minimum volumetric wear. Similar observations have been reported by various researchers in regard to the effect of MD as filler on the wear performance of polymer composites [45,46]. Authors claimed that wear resistance was remained highest with the combination of lower sliding distance, sliding velocity, normal load with higher MD filled polymer composites.…”
Section: Sliding Wear Analysissupporting
confidence: 87%
“…Analysis of these results leads to the conclusion that combination of factors A4 (20 wt% MD), B1 (400 m sliding distance), C1 (1 m/s sliding velocity) and D1 (10 N normal load) gives minimum volumetric wear. Similar observations have been reported by various researchers in regard to the effect of MD as filler on the wear performance of polymer composites [45,46]. Authors claimed that wear resistance was remained highest with the combination of lower sliding distance, sliding velocity, normal load with higher MD filled polymer composites.…”
Section: Sliding Wear Analysissupporting
confidence: 87%
“…40 The reason reported by authors for such wear mechanism is more brittleness of the composite at higher MD content with no plastic deformation and where only wear debris is found. 40 Sharma et al studied the effect of MD reinforcement (0-30 wt%) on needle-punched nonwoven epoxy composites by examining the erosion wear rate mechanism. Their study concluded that the addition of MD filler has provided an improved erosion wear resistance.…”
Section: Effect Of Marble Dust On Tribological Propertiesmentioning
confidence: 96%
“…At higher reinforcement of MD, short and continuous wear tracks are visible while low content of MD results in micro-fracture and plastic deformation in composites (see Figure 8). 40 The reason reported by authors for such wear mechanism is more brittleness of the composite at higher MD content with no plastic deformation and where only wear debris is found. 40 Sharma et al studied the effect of MD reinforcement (0-30 wt%) on needle-punched nonwoven epoxy composites by examining the erosion wear rate mechanism.…”
Section: Effect Of Marble Dust On Tribological Propertiesmentioning
confidence: 96%
“…Work [11] designed new polymeric composites with a filler in the form of waste of marble dustsolid waste. This waste forms when cutting and polishing marble pieces at construction sites, as well as at marble processing enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the coefficient of thermal conductivity of the composites increases with an increase in filler content. Similar to works [9][10][11], the impact of natural factors on the stability of the composite was not tackled.…”
Section: Introductionmentioning
confidence: 99%